2014
DOI: 10.1109/tbme.2014.2324998
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Registration of Real-Time and Prior MRI Data for Image-Guided Cardiac Interventions

Abstract: Recently, there is a growing interest in using magnetic resonance imaging (MRI) to guide interventional procedures due to its excellent soft tissue contrast and lack of ionizing radiation compared to traditional radiographic guidance. One of these applications is the use of MRI to guide radio frequency ablation of anatomic substrates, within the left ventricle, responsible for ventricular tachycardia. However, different MRI acquisition schemes have significant tradeoffs between image quality and acquisition ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Po Su et al (2013) applied SSD on both image intensities and gradients, combining them in a unique similarity measure. In (Xu et al, 2014b), the matching criterion was defined using the normalized gradient field of the images, while CC of both intensity and gradient magnitude was adopted in (Xu et al, 2008). In (Lin et al, 2013), a merit function called Weighted Edge-Matching Score (WEMS) was used to evaluate the similarity of a 2D real-time image and the corresponding reformated slice to search for the 3D pose of a bone model.…”
Section: Iconicmentioning
confidence: 99%
See 1 more Smart Citation
“…Po Su et al (2013) applied SSD on both image intensities and gradients, combining them in a unique similarity measure. In (Xu et al, 2014b), the matching criterion was defined using the normalized gradient field of the images, while CC of both intensity and gradient magnitude was adopted in (Xu et al, 2008). In (Lin et al, 2013), a merit function called Weighted Edge-Matching Score (WEMS) was used to evaluate the similarity of a 2D real-time image and the corresponding reformated slice to search for the 3D pose of a bone model.…”
Section: Iconicmentioning
confidence: 99%
“…The standard way to estimate 6-DOF rigid transformations, consists in minimizing an energy functional (based on an iconic or geometric matching criterion) often with a continuous optimization algorithm (see section 4.1) where the search space is part of the Euclidean group SE(3) of rigid transformations. Sensors as described in section 2.3 can be used as well for rigid alignment as proposed in a number of papers (Chandler et al, 2008;Elen et al, 2010;Fei et al, 2002Fei et al, , 2003aFrühwald et al, 2009;Fuerst et al, 2014;Gholipour et al, 2010;Huang et al, 2009;Jiang et al, 2007a;Kainz et al, 2015;Kim et al, 1999Kim et al, , 2010aNir and Tannenbaum, 2011;Penney et al, 2004a;Rousseau et al, 2006;Smolíková Wachowiak et al, 2005;Xu et al, 2014b;Yeo et al, 2004;Yu et al, 2011;Chen et al, 2016).…”
Section: Rigidmentioning
confidence: 99%
“…For this, a weighted total variation flow algorithm was used to extract coarse-to-fine features from the input images and subsequently register the corresponding scale images in a hierarchical manner. 87 The registration method yielded a corresponding model that was used to characterize the respiratory motion during an MRI-guided ablation study. 88 Further, accelerating the registration algorithm with a GPU-based implementation facilitated updating the respiratory motion model every heart beat to account for potential intraprocedural changes.…”
Section: Image Analysismentioning
confidence: 99%
“…also demonstrated that existing MRI scans can serve as prior images to improve the quality of CS reconstruction. It has been shown that prior images can promote both the contrast and signal‐to‐noise ratio (SNR) of the reconstruction results . In addition, Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that prior images can promote both the contrast and signal-to-noise ratio (SNR) of the reconstruction results. 41 In addition, Chen et al [42][43][44] developed the prior image constrained compressed sensing (PICCS) method for dynamic CT imaging with few views of projections. The subtraction of the target image with the prior image is sparser than the target image, so PICCS utilizes the sparsity of the subtracted image to improve the reconstruction quality.…”
Section: Introductionmentioning
confidence: 99%